Stabilizing postwar Europe: Aligning domestic and international goals - Armin Schäfer (Max Planck Institute for the Study of Societies, 2003)
This paper looks at the historical developments that led to the Schuman Plan in 1950, which today is seen as a starting signal for the European integration process. It argues that this announcement by the French foreign minister constituted a genuine change of strategy that can only be understood in the light of the preceding historical chain of events. The first steps of European integration were part of a search for suitable institutions capable of dealing with Europe's economic and political problems, which also involved the Bretton Woods institutions, Marshall Aid and the OEEC, and, finally, the ECSC. These organizations' respective fate depended on the strategies of key states, which in turn were driven by domestic concerns. Aligning their interests took several steps and was only completed when all three organizations existed in parallel. Throughout this process, all states had to abandon their preferred course of action and learn to settle for second best. – – Dieses Papier betrachtet die historischen Ereignisse, die 1950 zur Bekanntgabe des Schuman-Plans führten, der heute als Startschuss der europäischen Integration angesehen wird. Es argumentiert, dass Schumans Initiative ein dramatischer Strategiewechsel zugrunde lag, der nur vor dem Hintergrund der vorangegangenen historischen Sequenz verstanden werden kann. Die ersten Schritte europäischer Integration waren aus dieser Sicht Teil einer umfassenderen Suche nach institutionellen Lösungen für Europas ökonomische und politische Probleme. An ihr waren die Bretton Woods-Institutionen, die Marshall-Hilfe und die OEEC sowie schließlich die EGKS beteiligt. Der Erfolg dieser Organisationen hing vom Verhalten der wichtigsten Staaten ihnen gegenüber ab, welches wiederum durch innenpolitische Überlegungen bestimmt war. Ihre Interessen in Einklang miteinander zu bringen, benötigte mehrere Anläufe und war erst abgeschlossen, als alle drei Organisationen nebeneinander bestanden. Im Verlauf dieses Prozesses mussten alle Staaten lernen, dass die von ihnen bevorzugte Entwicklung nicht mehr länger möglich war, und aus ihrer Sicht zweitbeste Lösungen akzeptieren.
Keywords: 300